2020
DOI: 10.1097/ccm.0000000000004353
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned ICU Admission From Hospital Wards After Rapid Response Team Review in Australia and New Zealand

Abstract: Objectives: To evaluate what proportion of unplanned ICU admissions from hospital wards occurred after rapid response team review and compare baseline characteristics and outcomes of patients admitted after rapid response team review with non-rapid response team-related admissions. Design: Multicenter binational retrospective cohort study. Setting: One-hundred seventy-eight ICUs across Australia and New Zeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Covariates considered as potential confounders of hospital outcomes based on previous studies were extracted from the KSA database [ 8 , 24 , 25 ]. These variables included demographic factors such as age, sex, and body mass index (BMI), comorbidities, suspected infection site, blood culture positivity, including multidrug-resistant (MDR) pathogens, and measures of illness severity, such as the presence of septic shock, serum lactate level, or the sequential organ failure assessment score (SOFA).…”
Section: Methodsmentioning
confidence: 99%
“…Covariates considered as potential confounders of hospital outcomes based on previous studies were extracted from the KSA database [ 8 , 24 , 25 ]. These variables included demographic factors such as age, sex, and body mass index (BMI), comorbidities, suspected infection site, blood culture positivity, including multidrug-resistant (MDR) pathogens, and measures of illness severity, such as the presence of septic shock, serum lactate level, or the sequential organ failure assessment score (SOFA).…”
Section: Methodsmentioning
confidence: 99%
“…Ten studies identified respiratory symptoms, specifically tachypnea at >25 breaths per minute and oxygen saturation at <90%, as the top triggers for RRT activation (Byrne et al, 2021;Churpek et al, 2017;Considine et al, 2017;Currey et al, 2022;Fernando et al, 2019;Lyons et al, 2019;Sebat et al, 2020;Shappell et al, 2018;Tirkkonen et al, 2017;Viana et al, 2021). The RRT was also activated for new-onset breathing difficulty, bradypnea, acute respiratory distress, chronic respiratory disease, and complex respiratory failure (Byrne et al, 2021;Fernando et al, 2019;Lyons et al, 2019;Na et al, 2020;Orosz et al, 2020;Shappell et al, 2018;Smith et al, 2017;Tirkkonen et al, 2017;Viana et al, 2021). Cardiovascular was the second most common activation category, with six studies identifying these issues as the top concern for RRT activation (Kim et al, 2021;Na et al, 2020;Padilla & Mayo, 2019;Sebat et al, 2020;Shoaib et al, 2021;Smith et al, 2017).…”
Section: Adult Triggersmentioning
confidence: 99%
“…Overall ICU and hospital mortality rates were 12.3% (51/413) and 13.6% (56/411) respectively, with no significant difference between the groups. Even though the ICU length of stay was similar between the two groups (median, 6 days; IQR, 3-16 days), patients in the RRT review group had a longer hospital length of stay (median, 18 [IQR, 11-33] v 13 days [IQR, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]; P < 0.001). The hospital readmission rate was 16.2%, which was similar between the groups (Table 3).…”
Section: Outcome Data Based On Prior Rrt Reviewmentioning
confidence: 99%